Solve √3x

^{2}- √2x +3√3=0.Solve √3x^{2} - √2x +3√3=0.

Tutors, please sign in to answer this question.

Bridgewater, NJ

Use the quadratic equation to solve this equation:

x = -b + square root of (b^{2} - 4ac) divided by 2a where a = radical 3, b = -radical 2, and c = 3 radical 3

If you plug in all these values in the quadratic equation you will get the following answer:

x = (radical 2 + radical of -34) divided by 2 radical 3

radical of -1 equals i (imaginary number)

Therefore x = (radical 2 + i radical of 34) divided by 2 radical 3.

- Inequalities 382
- Algebra 1 4075
- Math 9867
- Math Help 5452
- Word Problem 5121
- Algebra 5059
- Algebra 2 3503
- Word Problems 1475
- Word Problem Help 1163
- Business Math 264